Intraventricular haemorrhage (IVH) and associated clinical characteristics in outborn preterm infants - Saumil Desai; Maria Joseph; Kevin George; Kai Ning Tan; Zac Dempsey; Matthew Cooper; Scott White; Mary Sharp; Jonathan Davis (BMJ Open, 2026)
Objectives To evaluate maternal, infant and transport factors associated with intraventricular haemorrhage (IVH) in outborn preterm infants